Weighted Average Method in Evolving the Nutrient Status of Soils Under Cropping Systems Involving Tuber Crops in AEU 3 and AEU 9 of Kerala - P. S., Anju; Susan, John; S. B., Ray (JOURNAL OF ROOT CROPS, 2020)
Agro ecological unit (AEU) 3 and AEU 9 are the two major tuber crops growing regions of Kerala cultivating tuber crops like cassava, yams and aroids mostly as intercrops in coconut gardens. Nutrient status of the soils of AEU’s are determined for making proper fertilizer recommendation to avoid both under-use and over-use of nutrients thereby attaining monetary gain as well as soil health protection by avoiding excess nutrient application. In arriving at proper nutrient status of the soils of the AEU’s, determining the weighted average nutrient status of the AEU’s with respect to the mean nutrient status and area of the panchayats/blocks was found better. It can be more meaningful and realistic from the point of view of arriving at the fertilizer recommendation to crops cultivating in that AEU’s. In this paper, as a prelude to formulate customized fertilizers for elephant foot yam (EFY) under intercropping in the coconut gardens of these two AEU’s, the weighted average data on pH, EC, organic carbon (OC), available N, P, K, Ca, Mg, S, Fe, Cu, Mn, Zn and B based on the nutrient status of the soils collected from 43 and 161 panchayats and their respective areas under AEU 3 and AEU 9 were determined. The values for AEU 3 and AEU 9 respectively were 5.85 for both AEU’s (pH), 0.291 and 0.310 dSm-1 (EC), 0.945 and 1.502% (OC), 61.97 and 69.27 kg ha-1 (available P), 213.96 and 295.87 kg ha-1 (available K), 113.32 and 600.16 ppm (exchangeable Ca), 37.53 and 114.99 ppm (exchangeable Mg), 5.07 and 21.46 ppm (available S), 3.94 and 5.68 ppm (available Zn), 0.698 and 0.816 ppm (available B), 1.79 and 3.79 ppm (available Cu), 101.20 and 64.66 ppm (available Fe) and 18.82 and 37.65 ppm (available Mn). The weighted average data of the two AEU’s indicated drastic variation in the nutrient status between the two AEU’s in the case of most of the parameters. The weighted average nutrient data of the two AEU’s clearly indicated the suitability of the soils of both AEU’s for EFY cultivation especially AEU 9 as they are rich in organic carbon as well as other essential nutrients. Moreover, this data formed a basis for fixing the theoretical optimum of soil test based nutrient recommendation to derive the practical optimum based on nutrient omission and nutrient level experiments in formulating the customized fertilizers for EFY.